The dark side of coaching: the negative affect of athletes as a mediator in the impact of abusive supervision on their performance and turnover - Lin, P.-Y.; Chiu, B. W.; Wang, I.-A. (International Journal of Sport Psychology, 2025)
Drawing from the affective events theory, this study investigated the impact of abusive supervision by coaches on athletes` practice performance and turnover intention, with a focus on the mediating role of negative affect. A total of 302 student-athletes in Taiwan were recruited via convenience sampling. The data were analyzed by running partial least squares structural equation modeling to test the hypothesized relationships. The results indicated that abusive supervision had a significant negative impact on practice performance and a significant positive impact on turnover intention. These relationships were partially mediated by negative affect, suggesting that the adverse effects of abusive supervision on athletes` performance and turnover intention are, in part, due to the negative emotional states elicited by such supervisory behaviors. This study underscores the need for interventions aimed at promoting supportive coaching practices and addressing athletes` emotional well-being to mitigate the unfavorable effects of abusive supervision.